Fortune's fool - Lackey, Mercedes (New York : Luna Books, 2008)
When Ekaterina, the seventh daughter of the Sea King, uses her special ability to move around on land to serve as her father's spy, she is kidnapped, along with other princesses, and held hostage in a castle where her only hope for rescue lies within a man thought to be a fool.
99890
Keywords: Jinn; Princesses; Princes; Fantasy fiction